Work Stress Role in Mediating the Relationship of Multiple Role Conflict Toward to Performance - Eka Darmi Pratiwi; Putu Ngurah Suyatna Yasa; Ni Wayan Sitiari (JUSTBEST: Journal of Sustainable Business and Management, 2021)
This study aims to analyze and explain the effect of multiple role conflict toward to the employee’s performance with work stress as a mediating variable with female employees of the Denpasar City Education and Job Training Institution as subject of research. The research design used to answer this problem was quantitative with a sample size of 48 people by using the saturated sample method. The data used in this study are primary and secondary both quantitative and qualitative data. Data analyzed by using structural equation modeling (SEM) with the partial least square (PLS) method which obtained the following research results: 1) Multiple role conflict has a positive but not significant effect on employee’s performance at the Denpasar City Education and Job Training Institution. 2) Multiple role conflict has a positive effect on work stress of female employees at the Denpasar City Education and Job Training Institution. 3) Job stress has a positive and not significant effect on employee performance at the Denpasar City Education and Job Training Institution. 4) Work stress is not a mediator of the influence of multiple role conflict on the female employee performance of Denpasar City Education and Job Training Institution.